Crystal keepers - Mull, Brandon, 1974- (Mull, Brandon, 1974- Five Kingdoms, 2015)
Cole Randolph ventures to a new kingdom as he continues his search for his friends -- and also pursues his quest to mend what has gone awry with the magic in The Outskirts.